158k views
3 votes
Solve each for X. Show your work


3(2x - 1) + 2(x + 5) = 47

User Dsrdakota
by
6.3k points

2 Answers

6 votes

Answer:

x = 5

Explanation:


3(2x - 1) + 2(x + 5) = 47


6x - 3 + 2(x + 5) = 47


6x - 3 + 2x + 10 = 47


8x - 3 + 10 = 47


8x + 7 = 47


8x = 47 - 7


8x = 40


(8x / 8 = 40 / 8 = x = 40 / 8 )


x = 5

User Acontell
by
5.4k points
3 votes

3(2x - 1) + 2(x + 5) = 47

6x - 3 + 2x + 10 = 47

6x + 2x = 47 + 3 - 10

8x = 40 / : 8

x = 5 ← the end

User Orbitcowboy
by
6.5k points